The role of RhoA/Rho kinase pathway in endothelial dysfunction - Yao, Lin (Medknow Publications, 2010)
Endothelial dysfunction is a key event in the development of vascular disease, and it precedes clinically obvious vascular pathology. Abnormal activation of the RhoA/Rho kinase (ROCK) pathway has been found to elevate vascular tone through unbalancing the production of vasodilating and vasoconstricting substances. Inhibition of the RhoA/ROCK pathway can prevent endothelial dysfunction in a variety of pathological conditions. This review, based on recent molecular, cellular, and animal studies, focuses on the current understanding of the ROCK pathway and its roles in endothelial dysfunction.